Beyond the target: implications of Wnt pathway inhibitors on bone health - Clement Nachef; Arnaud Vanjak; Eric Haÿ; Martine Cohen-Solal; Thomas Funck-Brentano (Journal of Molecular Medicine, 2026)
Wnt signaling inhibitors are under investigation as potential therapies for conditions characterized by upregulated Wnt signaling, such as cancers, hematological disorders, and organ fibrosis. However, because the Wnt pathway is essential for bone homeostasis, its inhibition can adversely affect skeletal health. This review focuses on the bone-related off-target effects of Wnt inhibitors currently in clinical development, specifically those evaluated in Phase I and II trials with available published data. We found that inhibitors targeting upstream components of the pathway—such as Wnt ligands or receptors (e.g., porcupine inhibitors, Ipafricept, or Vantictumab)—frequently lead to bone-related adverse effects, including fractures and early trial termination. Co-administration of bisphosphonates may help mitigate these effects. In contrast, downstream inhibitors (e.g., PRI-724, niclosamide) have not been linked to bone toxicity, although this may reflect either underreporting or a genuinely lower skeletal impact. Further preclinical studies are warranted to better understand these differential effects. A thorough understanding of bone-specific risks is critical as Wnt signaling inhibitors continue to advance in clinical development.

“Please, mind the gap”: A narrative review on digitalization gaps and barriers in the livestock sector - Anna Stygar; Jarkko K. Niemi; Tomas Norton; Halid Kayhan; Ana Maria Correa Harcus; Clement Allain; Adrien Lebreton; Vasileios Anestis; Thomas Bartzanas; Sotiria Vouraki; Georgios Arsenos; Matti Pastell (Computers and Electronics in Agriculture, 2026)

Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Growth, density, and property crime: A longitudinal county-level study in the USA, 2001–2007 - Matthew Thomas Clement; Nathan W. Pino; Nathaniel Dede-Bamfo; Jack DeWaard (The Social Science Journal, 2026)

Increased benthic biodiversity and food web recovery after decommissioning of oil and gas infrastructure - Zelin Chen; Tom C. Cameron; Elena Couce; Clement Garcia; Natalie Hicks; Gareth E. Thomas; Murray S. A. Thompson; Corinne Whitby; Eoin J. O'Gorman (Limnology and Oceanography, 2026)
There is a global increase in the decommissioning of offshore oil and gas (O&G) infrastructure at the end of its operating lifetime. However, there is strikingly limited empirical evidence for the environmental and ecological impacts of decommissioning. Here, we employed a meta‐analytical approach on an industry benthic monitoring database to investigate the benthic biodiversity and food web properties of structures sampled in the short term ( 5 yr; scenario 3) after decommissioning. We found reduced species richness and simplified food webs in scenario 1, followed by the first signs of recovery in scenario 2, with a slightly higher proportion of intermediate species and density of food web connections. Food webs recovered further in scenario 3, with a much greater density of interactions, but also more links and longer food chains, while a reduction in generalism and connectance indicated an increased prevalence of specialist species. Our findings demonstrate disturbance risks associated with the decommissioning process in the short term, but a positive recovery trajectory over longer timescales. We highlight the importance of industry collecting more extensive and long‐term data at multiple time points and covering different decommissioning types, establishing a standardized data workflow for integrating with available monitoring efforts, and improving stakeholder participation and data accessibility to support an environmentally sound decommissioning process.

Ecological recovery of benthic fauna from contamination near oil and gas platforms - Christopher P. Lynam; Clement Garcia; Zelin Chen; Gareth E. Thomas; Natalie Hicks; Stefan G. Bolam; Debbie J.F. Russell (Marine Pollution Bulletin, 2025)

Partial disruption of the Arabidopsis 2S seed storage proteins highlights the essential role of redox homeostasis in seed proteome plasticity and rebalancing - Clement Bagaza; Huda Ansaf; Abou Yobi; Kirk Czymmek; Thomas P. Mawhinney; Amanda Agosto Ramos; Daniel J. Kliebenstein; Dan H. Cohen; Hagai Yasuor; Ruthie Angelovici (Plant Science, 2025)

Offshore wind turbines constitute benthic secondary production hotspots on and around constructions - Jennifer Dannheim; Jan Beermann; Joop W.P. Coolen; Jan Vanaverbeke; Steven Degraer; Silvana N.R. Birchenough; Clement Garcia; Genevieve Lacroix; Dario Fiorentino; Han Lindeboom; Roland Krone; Hendrik Pehlke; et al. (Journal of Environmental Management, 2025)

Co‐Extinctions and Co‐Compensatory Species Responses to Climate Change Moderate Ecosystem Futures - Thomas J. Williams; Clement R. Garcia; Jasmin A. Godbold; Philippe Archambault; Martin Solan (Global Change Biology, 2025)
Consensus has been reached that the sequential loss of biodiversity leads to a non‐linear and accelerating decline in ecosystem properties. The form of this relationship, however, is based on theory and empirically derived observations that do not include species co‐extinctions. Here, we use data from marine benthic invertebrate communities to parameterise trait‐based extinction models that adjust the probability of species extirpation and compensation by including the dependencies between different species across a gradient of climate‐driven environmental change. Our simulations reveal that the inclusion of static co‐extinctions leads to more pronounced declines in the trajectories of sediment bioturbation—a process of great importance to the functioning of marine ecosystems—than those observed with sequential losses of single species. Compensatory mechanisms and the allowance of the formation of new interactions derived from local and regional species pools moderate the compounding influence of co‐extinction but introduce additional variability in community response depending on the composition and functional role of incoming and outgoing species. Our observations emphasise the importance of accounting for local and regional community dynamics, especially in highly connected systems that are prone to extinction cascades when projecting the ecosystem consequences of altered biodiversity.

Leopards on the edge: Assessing population status, habitat use, and threats in Southeast Asia - S. Rostro-García; J.F. Kamler; R. Sollmann; G. Balme; R. Sukmasuang; A. Godfrey; S. Saosoong; K. Siripattaranukul; S. Suksavate; W. Thomas; R. Crouthers; V. In; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Participant Evaluation of a Multi-disciplinary Oncology Preceptorship Training Program for Oncology Health Professionals from Kumasi, Ghana - Kenneth W. Merrell; Thomas Okpoti Konney; Osei Acheamfour; Joseph Lucido; Abena Yeboah Aduse-Poku; Amanika Kumar; Mavis Bobie Ansah; Adu Tutu Amankwa; Dean Shumway; Fred Kwame Awittor; Augustina Badu-Peprah; Lionel Aurelien A. Kankeu Fonkoua; et al. (Journal of Cancer Education, 2024)
A critical shortage of skilled healthcare workers is a primary cause of disparate global cancer outcomes. We report participant evaluation of a multidisciplinary preceptorship program. In collaboration with the city of Kumasi, Ghana, Mayo Clinic and the City Cancer Challenge hosted a preceptorship program for comprehensive multidisciplinary breast and cervix cancer training. A total of 14 healthcare workers from Kumasi received two weeks of training at Mayo Clinic in November and December 2021. Each participant and preceptor were requested to complete an anonymous post-participation survey. Of the 14 trainee participants, 10 (71%) completed the survey. All respondents found the program “valuable and applicable to their clinical practice.” Ninety percent reported they were able to “review effective and critical elements in the development and expansion of the multidisciplinary team” and able to “solve practical clinical cases as a team”. General themes of satisfaction included: (1) organization and administration, (2) clinical observations and demonstrations, (3) guidelines development, and (4) recognizing the central importance of cultivating a team-based approach. Of the 40 preceptors, 16 (40%) completed the survey. All respondents reported they felt the training would meaningfully “influence patient care in Ghana”, that participation “added value or joy to their clinical practice,” and all wished to “participate in future preceptorship programs”. After a focused two-week program, trainees reported high satisfaction, usefulness from observing specialized cancer care, and value in closely observing a multidisciplinary oncology team. Preceptors reported the experience added joy and perspective to their clinical practice and wished to participate in future programs.

Oil and gas platforms degrade benthic invertebrate diversity and food web structure - Zelin Chen; Tom C. Cameron; Elena Couce; Clement Garcia; Natalie Hicks; Gareth E. Thomas; Murray S.A. Thompson; Corinne Whitby; Eoin J. O'Gorman (Science of The Total Environment, 2024)

Assessment of the tolerance angle for pedicle screw insertion - Lugdivine Leblond; Yves Godio-Raboutet; Yann Glard; Raphael La Greca; Thomas Clement; Morgane Evin (Medical & Biological Engineering & Computing, 2024)

Revisiting ecological carrying capacity indices for bivalve culture - Luc A. Comeau; Thomas Guyondet; David Drolet; Rémi Sonier; Jeff C. Clements; Réjean Tremblay; Ramón Filgueira (Aquaculture, 2023)

Sustained secretion of human growth hormone from TheraCyte devices encapsulated with PiggyBac-engineered retinal pigment epithelium cells - Claudia R. Cecchi; Sidsel Alsing; Gustavo P.P. Jesus; Enio A. Zacarias; Lisbeth Kjaer; Michelle S. Clement; Makiko Kumagai-Braesch; Thomas J. Corydon; Paolo Bartolini; Cibele N. Peroni; Lars Aagaard (Tissue and Cell, 2023)

Geochemical assessment and pollution evaluation of stream sediments’ quality impacted by industrial activities at Suame Magazine area, Kumasi, Ghana - Josephine Adu-Gyamfi; Emmanuel Kwesi Nyantakyi; Julius Kwame Borkloe; Prodeo Yao Agbotui; Saeed Ibn Idris Kofi Yeboah; Nana Osei Bonsu Ackerson; Emmanuel Acheaw; Clement Apuri Wezenamo; Martin Kyereh Domfeh; Emmanuel Nsiah; Thomas Ntori; Ebenezer Gyamfi (Arabian Journal of Geosciences, 2023)

Taphonomic and diagenetic implications of reduction spot formation in Cretaceous red beds from the Jiaolai Basin, Eastern China - Wenzhao Fu; Peter Turner; Thomas Clements; Alan R.T. Spencer; Jifeng Yu; Yu Yang; Bangjie Guo; Zhenguo Ning; Xizhun Zhuo; Michael S. Riley; Jason Hilton (Journal of Asian Earth Sciences, 2023)

Towards the fully automated monitoring of ecological communities - Marc Besson; Jamie Alison; Kim Bjerge; Thomas E. Gorochowski; Toke T. Høye; Tommaso Jucker; Hjalte M. R. Mann; Christopher F. Clements (Ecology Letters, 2022)
High‐resolution monitoring is fundamental to understand ecosystems dynamics in an era of global change and biodiversity declines. While real‐time and automated monitoring of abiotic components has been possible for some time, monitoring biotic components—for example, individual behaviours and traits, and species abundance and distribution—is far more challenging. Recent technological advancements offer potential solutions to achieve this through: (i) increasingly affordable high‐throughput recording hardware, which can collect rich multidimensional data, and (ii) increasingly accessible artificial intelligence approaches, which can extract ecological knowledge from large datasets. However, automating the monitoring of facets of ecological communities via such technologies has primarily been achieved at low spatiotemporal resolutions within limited steps of the monitoring workflow. Here, we review existing technologies for data recording and processing that enable automated monitoring of ecological communities. We then present novel frameworks that combine such technologies, forming fully automated pipelines to detect, track, classify and count multiple species, and record behavioural and morphological traits, at resolutions which have previously been impossible to achieve. Based on these rapidly developing technologies, we illustrate a solution to one of the greatest challenges in ecology: the ability to rapidly generate high‐resolution, multidimensional and standardised data across complex ecologies.

Therapeutic Reference Range for Aripiprazole in Schizophrenia Revised: a Systematic Review and Metaanalysis - Xenia M. Hart; Christoph Hiemke; Luzie Eichentopf; Xenija M. Lense; Hans Willi Clement; Andreas Conca; Frank Faltraco; Vincenzo Florio; Jessica Grüner; Ursula Havemann-Reinecke; Espen Molden; Michael Paulzen; et al. (Psychopharmacology, 2022)
Rationale While one of the basic axioms of pharmacology postulates that there is a relationship between the concentration and effects of a drug, the value of measuring blood levels is questioned by many clinicians. This is due to the often-missing validation of therapeutic reference ranges. Objectives Here, we present a prototypical meta-analysis of the relationships between blood levels of aripiprazole, its target engagement in the human brain, and clinical effects and side effects in patients with schizophrenia and related disorders. Methods The relevant literature was systematically searched and reviewed for aripiprazole oral and injectable formulations. Population-based concentration ranges were computed ( N = 3,373) and pharmacokinetic influences investigated. Results Fifty-three study cohorts met the eligibility criteria. Twenty-nine studies report blood level after oral, 15 after injectable formulations, and nine were positron emission tomography studies. Conflicting evidence for a relationship between concentration, efficacy, and side effects exists (assigned level of evidence low, C; and absent, D). Population-based reference ranges are well in-line with findings from neuroimaging data and individual efficacy studies. We suggest a therapeutic reference range of 120–270 ng/ml and 180–380 ng/ml, respectively, for aripiprazole and its active moiety for the treatment of schizophrenia and related disorders. Conclusions High interindividual variability and the influence of CYP2D6 genotypes gives a special indication for Therapeutic Drug Monitoring of oral and long-acting aripiprazole. A starting dose of 10 mg will in most patients result in effective concentrations in blood and brain. 5 mg will be sufficient for known poor metabolizers.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

The uneven weight of carbon on policy: towards a framework for understanding how greenhouse gas inventories can inform equitable climate policy design - Andrew Pattison; Mathew Thomas Clement; Robert Habans (Journal of Environmental Studies and Sciences, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Pharmacological intervention in young adolescents rescues synaptic physiology and behavioural deficits in Syngap1+/− mice - Vijaya Verma; M. J. Vijay Kumar; Kavita Sharma; Sridhar Rajaram; Ravi Muddashetty; Ravi Manjithaya; Thomas Behnisch; James P. Clement (Experimental Brain Research, 2022)

Effects of habitat complexity on giant water bug (Belostoma) functional response to rams-horn snail prey (Helisoma) - Joe C. Gunn; Sarah J. Clements; Jessica T. Kansman; Jacob A. Cianci-Gaskill; Thomas L. Anderson (Hydrobiologia, 2021)

The killer within: Endogenous bacteria accelerate oyster mortality during sustained anoxia - Michael R. S. Coffin; Jeff C. Clements; Luc A. Comeau; Thomas Guyondet; Michelle Maillet; Laura Steeves; Keryn Winterburn; José M. F. Babarro; Martin A. Mallet; Rémy Haché; Luke A. Poirier; Saswati Deb; et al. (Limnology and Oceanography, 2021)
Sustained periods of anoxia, driven by eutrophication, threaten coastal marine systems and can lead to mass mortalities of even resilient animals such as bivalves. While mortality rates under anoxia are well‐studied, the specific mechanism(s) of mortality are less clear. We used a suite of complementary techniques (LT50, histology, 16S rRNA amplicon sequencing, and valvometry) to show that the proliferation of anaerobic bacteria within eastern oysters ( Crassostrea virginica ) accelerates mortality rate under anoxic conditions. Manipulative laboratory experiments revealed that oyster survival under anoxic conditions was halved when bacteria were present compared to when they were excluded by the broad‐spectrum antibiotic chloramphenicol. Histological assessments supported this mechanism and showed infiltration of bacteria in oysters that were not treated with antibiotics compared to a general lack of bacteria when oysters were treated with antibiotics. 16S rRNA amplicon sequencing failed to identify any particular genera of bacteria responsible for mortality, rather a diversity of endogenous anaerobic and/or sulfate‐reducing bacteria were common among oysters. In addition, monitoring of oyster valve gaping behavior in the field revealed that oysters showed remarkable valve closure synchrony when first exposed to anoxia. However, oysters periodically opened throughout anoxia/hypoxia in both the lab and field, suggesting that the infiltration of exogenous bacteria from the environment may also influence mortality rates under natural settings. Coupled with previous studies, we posit that mass mortality events in a wide range of coastal bivalves are likely the result of co‐morbidity from asphyxiation and bacterial processes.

GliMR: Cross-Border Collaborations to Promote Advanced MRI Biomarkers for Glioma - Patricia Clement; Thomas Booth; Fran Borovečki; Kyrre E. Emblem; Patrícia Figueiredo; Lydiane Hirschler; Radim Jančálek; Vera C. Keil; Camille Maumet; Yelda Özsunar; Cyril Pernet; Jan Petr; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose There is an annual incidence of 50,000 glioma cases in Europe. The optimal treatment strategy is highly personalised, depending on tumour type, grade, spatial localization, and the degree of tissue infiltration. In research settings, advanced magnetic resonance imaging (MRI) has shown great promise as a tool to inform personalised treatment decisions. However, the use of advanced MRI in clinical practice remains scarce due to the downstream effects of siloed glioma imaging research with limited representation of MRI specialists in established consortia; and the associated lack of available tools and expertise in clinical settings. These shortcomings delay the translation of scientific breakthroughs into novel treatment strategy. As a response we have developed the network “Glioma MR Imaging 2.0” (GliMR) which we present in this article. Methods GliMR aims to build a pan-European and multidisciplinary network of experts and accelerate the use of advanced MRI in glioma beyond the current “state-of-the-art” in glioma imaging. The Action Glioma MR Imaging 2.0 (GliMR) was granted funding by the European Cooperation in Science and Technology (COST) in June 2019. Results GliMR’s first grant period ran from September 2019 to April 2020, during which several meetings were held and projects were initiated, such as reviewing the current knowledge on advanced MRI; developing a General Data Protection Regulation (GDPR) compliant consent form; and setting up the website. Conclusion The Action overcomes the pre-existing limitations of glioma research and is funded until September 2023. New members will be accepted during its entire duration.

Corrigendum: Reconstructing Global Chlorophyll-a Variations Using a Non-linear Statistical Approach - Elodie Martinez; Thomas Gorgues; Matthieu Lengaigne; Clement Fontana; Raphaëlle Sauzède; Christophe Menkes; Julia Uitz; Emanuele Di Lorenzo; Ronan Fablet (Frontiers in Marine Science, 2020)

Regulation of nitrogen fixation from free-living organisms in soil and leaf litter of two tropical forests of the Guiana shield - Leandro Van Langenhove; Thomas Depaepe; Sara Vicca; Joke van den Berge; Clement Stahl; Elodie Courtois; James Weedon; Ifigenia Urbina; Oriol Grau; Dolores Asensio; Josep Peñuelas; Pascal Boeckx; et al. (Plant and Soil, 2020)

Carbon emissions and climate policy support by local governments in California: a qualitative comparative analysis at the county level - Robert Habans; Matthew Thomas Clement; Andrew Pattison (Journal of Environmental Studies and Sciences, 2019)

Global Observations of Fine-Scale Ocean Surface Topography With the Surface Water and Ocean Topography (SWOT) Mission - Rosemary Morrow; Lee-Lueng Fu; Fabrice Ardhuin; Mounir Benkiran; Bertrand Chapron; Emmanuel Cosme; Francesco d’Ovidio; J. Thomas Farrar; Sarah T. Gille; Guillaume Lapeyre; Pierre-Yves Le Traon; Ananda Pascual; et al. (Frontiers in Marine Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Comparison of Health Communication Channels for Reaching Hispanics About Biobanking: a Pilot Trial - Jessica McIntyre; Julio Jiménez; Yonaira M. Rivera; Steven K. Sutton; Gloria Asencio; Eida M. Castro-Figueroa; Clement K. Gwede; Thomas H. Brandon; Susan T. Vadaparampil; Vani N. Simmons; Johanna Corchado; Laura Moreno; et al. (Journal of Cancer Education, 2018)

Community Engagement for Identifying Cancer Education Needs in Puerto Rico - Julio Jiménez; Axel Ramos; Francisco E. Ramos-Rivera; Clement Gwede; Gwendolyn P. Quinn; Susan Vadaparampil; Thomas Brandon; Vani Simmons; Eida Castro (Journal of Cancer Education, 2018)

Redox status and sperm characteristics in 1,4-dinitrobenzene-induced reproductive toxicity in Wistar rats - Janet Olayemi Sangodele; Mary Tolulope Olaleye; Thomas K. Monsees; Afolabi Clement Akinmoladun (Toxicology and Environmental Health Sciences, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Orchid historical biogeography, diversification, Antarctica and the paradox of orchid dispersal - Thomas J. Givnish; Daniel Spalink; Mercedes Ames; Stephanie P. Lyon; Steven J. Hunter; Alejandro Zuluaga; Alfonso Doucette; Giovanny Giraldo Caro; James McDaniel; Mark A. Clements; Mary T. K. Arroyo; Lorena Endara; et al. (Journal of Biogeography, 2016)
Aim Orchidaceae is the most species‐rich angiosperm family and has one of the broadest distributions. Until now, the lack of a well‐resolved phylogeny has prevented analyses of orchid historical biogeography. In this study, we use such a phylogeny to estimate the geographical spread of orchids, evaluate the importance of different regions in their diversification and assess the role of long‐distance dispersal ( LDD ) in generating orchid diversity. Location Global. Methods Analyses use a phylogeny including species representing all five orchid subfamilies and almost all tribes and subtribes, calibrated against 17 angiosperm fossils. We estimated historical biogeography and assessed the importance of different regions for rates of speciation, extinction and net species diversification. We evaluated the impact of particular LDD events on orchid diversity by asking how many species evolved in the new range subsequent to those events. Results Orchids appear to have arisen in Australia 112 Ma (95% higher probability distribution: 102.0–120.0 Ma), then spread to the Neotropics via Antarctica by 90 Ma ( HPD : 79.7–99.5 Ma), when all three continents were in close contact and apostasioids split from the ancestor of all other orchids. Ancestors of vanilloids, cypripedioids and orchidoids+epidendroids appear to have originated in the Neotropics 84–64 Ma. Repeated long‐ and short‐distance dispersal occurred through orchid history: stochastic mapping identified a mean total of 74 LDD events or 0.8 Ma −1 . Across orchid history, Southeast Asia was the most important source and maximally accelerated net diversification; across epidendroids, the Neotropics maximally accelerated diversification. Main conclusions Our analysis provides the first biogeographical history of the orchids, implicating Australia, the Neotropics and Antarctica in their origin. LDD and life in the Neotropics – especially the Andes – had profound effects on their spread and diversification; > 97% of all orchid species are restricted to individual continents.

Quantifying landscape‐level methane fluxes in subarctic Finland using a multiscale approach - Iain. P. Hartley; Timothy. C. Hill; Thomas. J. Wade; Robert. J. Clement; John. B. Moncrieff; Ana. Prieto‐Blanco; Mathias. I. Disney; Brian. Huntley; Mathew. Williams; Nicholas. J. K. Howden; Philip. A. Wookey; Robert. Baxter (Global Change Biology, 2015)
Quantifying landscape‐scale methane ( CH 4 ) fluxes from boreal and arctic regions, and determining how they are controlled, is critical for predicting the magnitude of any CH 4 emission feedback to climate change. Furthermore, there remains uncertainty regarding the relative importance of small areas of strong methanogenic activity, vs. larger areas with net CH 4 uptake, in controlling landscape‐level fluxes. We measured CH 4 fluxes from multiple microtopographical subunits (sedge‐dominated lawns, interhummocks and hummocks) within an aapa mire in subarctic Finland, as well as in drier ecosystems present in the wider landscape, lichen heath and mountain birch forest. An intercomparison was carried out between fluxes measured using static chambers, up‐scaled using a high‐resolution landcover map derived from aerial photography and eddy covariance. Strong agreement was observed between the two methodologies, with emission rates greatest in lawns. CH 4 fluxes from lawns were strongly related to seasonal fluctuations in temperature, but their floating nature meant that water‐table depth was not a key factor in controlling CH 4 release. In contrast, chamber measurements identified net CH 4 uptake in birch forest soils. An intercomparison between the aerial photography and satellite remote sensing demonstrated that quantifying the distribution of the key CH 4 emitting and consuming plant communities was possible from satellite, allowing fluxes to be scaled up to a 100 km 2 area. For the full growing season (May to October), ~ 1.1–1.4 g CH 4 m −2 was released across the 100 km 2 area. This was based on up‐scaled lawn emissions of 1.2–1.5 g CH 4 m −2 , vs. an up‐scaled uptake of 0.07–0.15 g CH 4 m −2 by the wider landscape. Given the strong temperature sensitivity of the dominant lawn fluxes, and the fact that lawns are unlikely to dry out, climate warming may substantially increase CH 4 emissions in northern Finland, and in aapa mire regions in general.

Statistical trend and change-point analysis of land-cover-change patterns in East Africa - Dong-Yun Kim; Valerie Thomas; Jenny Olson; Matthew Williams; Nicolle Clements (International Journal of Remote Sensing, 2013)

Early Postnatal Ethanol Exposure: Glutamatergic Excitotoxic Cell Death During Acute Withdrawal - K. M. Clements; L. M. Smith; J. N. J. Reynolds; P. G. Overton; J. D. Thomas; R. M. Napper (Neurophysiology, 2012)

Genome-wide associated loci influencing interleukin (IL)-10, IL-1Ra, and IL-6 levels in African Americans - Fasil Tekola Ayele; Ayo Doumatey; Hanxia Huang; Jie Zhou; Bashira Charles; Michael Erdos; Jokotade Adeleye; Williams Balogun; Olufemi Fasanmade; Thomas Johnson; Johnnie Oli; Godfrey Okafor; et al. (Immunogenetics, 2012)

Formative Research on Perceptions of Biobanking: What Community Members Think - John S. Luque; Gwendolyn P. Quinn; Francisco A. Montel-Ishino; Mariana Arevalo; Shalanda A. Bynum; Shalewa Noel-Thomas; Kristen J. Wells; Clement K. Gwede; Cathy D. Meade (Journal of Cancer Education, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Misidentification of OLGA-PH-J/92, believed to be the only crustacean cell line - Lucy E. J. Lee; Mary Rose Bufalino; Andrew E. Christie; Marc E. Frischer; Thomas Soin; Clement K. M. Tsui; Robert H. Hanner; Guy Smagghe (In Vitro Cellular & Developmental Biology - Animal, 2011)

Enhancing Oncology Health Care Provider's Sensitivity to Cultural Communication to Reduce Cancer Disparities: A Pilot Study - Gwendolyn P. Quinn; Julio Jimenez; Cathy D. Meade; Teresita Muñoz-Antonia; Clement K. Gwede; Eida Castro; Susan T. Vadaparampil; Vani Nath Simmons; Jessica McIntyre; Theresa T. Crocker; Thomas H. Brandon (Journal of Cancer Education, 2011)

Cautious Optimism over Norway‐Indonesia REDD Pact - Gopalasamy Reuben Clements; Jeffrey Sayer; Agni K. Boedhihartono; Oscar Venter; Thomas Lovejoy; Lian Pin Koh; William F. Laurance (Conservation Biology, 2010)

Impact of Terrain Heterogeneity on Coherent Structure Properties: Numerical Approach - Clement Fesquet; Sylvain Dupont; Philippe Drobinski; Thomas Dubos; Christian Barthlott (Boundary-Layer Meteorology, 2009)

Pan‐European δ 13 C values of air and organic matter from forest ecosystems - Deborah Hemming; Dan Yakir; Per Ambus; Mika Aurela; Cathy Besson; Kevin Black; Nina Buchmann; Regis Burlett; Alessandro Cescatti; Robert Clement; Patrick Gross; André Granier; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ 13 C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ 13 C values derived from large‐scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem‐scale δ 13 C values. In this framework, we also tested the potential of δ 13 C in canopy air and plant organic matter to record regional‐scale ecophysiological patterns. Our network estimates for the mean δ 13 C of ecosystem respired CO 2 and the related ‘discrimination’ of ecosystem respiration, δ er and Δ er , respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ 13 C values derived from regional‐scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional‐scale atmospheric sampling programs generally capture ecosystem δ 13 C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δ er . From west to east, across the network, there was a general enrichment in 13 C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13 C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δ er values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature ( T a ), but not significantly with monthly average precipitation ( P m ). In contrast, in 2002 (a much wetter peak season), δ er was significantly related with T a , but not significantly with VPD and RH. The important role of plant physiological processes on δ er in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time‐lag analyses of δ er vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δ er and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δ er signal during this season. Organic matter δ 13 C results showed progressive 13 C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13 C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ 13 C values of organic matter of any of the plant components did not well represent short‐term δ er values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.